1987
DOI: 10.1177/004051758705700406
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Crystalline Phases in Chemically Treated Cotton Fibers

Abstract: This paper deals with the evaluation of crystal lattice transformations and decrys tallization brought about in cotton fibers by chemical treatments, using x-ray diffiaction techniques. Suitable indices have been evolved to quantify cellulose II and total crys tallinity values, and cotton fibers subjected to widely different chemical treatments have been evaluated. The accuracy of the new indices and their usefulness in routine analysis are enumerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 6 publications
2
6
0
Order By: Relevance
“…In this figure, it was seen that both WAXD patterns of jute fibers and NOCNF exhibited cellulose I structure having similar intensity distributions. Specifically, three similar diffraction peaks at 2θ angles of 16.5°, 22.7°, and 35.1° were seen in the two patterns, corresponding to (110), (200), and (004) reflections, respectively . This confirmed that the selected conditions in the nitro-oxidation reaction did not alter the crystal structure nor crystallinity in NOCNF when compared with those in untreated jute fibers.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…In this figure, it was seen that both WAXD patterns of jute fibers and NOCNF exhibited cellulose I structure having similar intensity distributions. Specifically, three similar diffraction peaks at 2θ angles of 16.5°, 22.7°, and 35.1° were seen in the two patterns, corresponding to (110), (200), and (004) reflections, respectively . This confirmed that the selected conditions in the nitro-oxidation reaction did not alter the crystal structure nor crystallinity in NOCNF when compared with those in untreated jute fibers.…”
Section: Resultssupporting
confidence: 62%
“…Specifically, three similar diffraction peaks at 2θ angles of 16.5°, 22.7°, and 35.1°were seen in the two patterns, corresponding to (110), (200), and (004) reflections, respectively. 41 This confirmed that the selected conditions in the nitro-oxidation reaction did not alter the crystal structure nor crystallinity in NOCNF when compared with those in untreated jute fibers. The crystallinity index (CI) calculated from the WAXD data using the Ruland method 40,41 for NOCNF was 69%, while that for jute fibers was 61%.…”
Section: CIsupporting
confidence: 65%
“…The crystallinity index of the treated fabrics and the powders was obtained by the formula Crl = ( (/12 2 + l2t.s)/2 -~ lll)/(112 + /21.5)/2, where Ix is the intensity measured at x degrees adapted from Cidambareswaran et al [6]. X-ray diagrams were obtained with a Philips analytical PW 1710 diffractometer and an x-ray tube using Ni filtered CuKa radiation.…”
Section: Methodsmentioning
confidence: 99%
“…Changes of internal structure 13 The changes in the specimen crystallinity and internal structure as a result of degradation were also investigated by using an X-ray diffractometer (M18XHF-SRA, Mac Science Co., Roswell, GA).…”
Section: Evaluation Of Biodegradabilitymentioning
confidence: 99%